2007
DOI: 10.1103/physreva.76.033201
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic generation from laser-irradiated clusters

Abstract: The harmonic emission from cluster nanoplasmas subject to short, intense infrared laser pulses is analyzed by means of particle-in-cell simulations. A pronounced resonant enhancement of the low-order harmonic yields is found when the Mie plasma frequency of the ionizing and expanding cluster resonates with the respective harmonic frequency. We show that a strong, nonlinear resonant coupling of the cluster electrons with the laser field inhibits coherent electron motion, suppressing the emitted radiation and re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 24 publications
4
48
0
Order By: Relevance
“…The nonlinearity of this process arises from the fact that the laser displaces the electron cloud relative to the ions. The electrons that are driven beyond the cluster surface feel a nonlinear restoring force, resulting in the creation of odd harmonic radiation [56,57]. For the cluster sizes investigated here, propagation effects do not play a major role in odd harmonic generation, as they are well described by electrostatic MD (see Fig.…”
Section: Microscopic Analysis Of Nonlinear Light Scatteringmentioning
confidence: 79%
“…The nonlinearity of this process arises from the fact that the laser displaces the electron cloud relative to the ions. The electrons that are driven beyond the cluster surface feel a nonlinear restoring force, resulting in the creation of odd harmonic radiation [56,57]. For the cluster sizes investigated here, propagation effects do not play a major role in odd harmonic generation, as they are well described by electrostatic MD (see Fig.…”
Section: Microscopic Analysis Of Nonlinear Light Scatteringmentioning
confidence: 79%
“…7,9,10,14 It may be noted that a pronounced resonant enhancement for NPs is found only for yields of the low-order harmonics, while the high-order harmonics completely disappear from the harmonic spectra in the simulations. 14 The controlled enhancement of low-order harmonics from 6 ϫ 10 5 -noble-gas clusters was discussed in Ref. 4.…”
Section: Application Of Nanoparticle-containing Laser Plasmas For Optmentioning
confidence: 86%
“…In the meantime, previous studies of harmonic generation in such objects were limited to exotic nanoclusters ͑Ar, Xe͒, which are formed in high-pressure gas jets due to rapid cooling by the adiabatic expansion. The physical origin of this process in the gas clusters [5][6][7][8][9][10][11][12][13][14][15] is mostly attributed to standard atomic harmonic generation, modified by the fact that in clusters the atoms are disposed to each other.…”
Section: Application Of Nanoparticle-containing Laser Plasmas For Optmentioning
confidence: 99%
“…Shim et al [29] observed this resonantly enhanced third harmonic generation from expanding clusters. Molecular dynamic (MD) and particle-in-cell (PIC) simulations [30,31] confirm the resonant enhancement of low-order harmonics, but show that high-order harmonics are suppressed because of the dynamical stochasticity of the electron motion caused by the nonlinear resonance.…”
Section: High-order Harmonic Generation From Various Sourcesmentioning
confidence: 99%